Jirga [videorecording (DVD)] - Gilmour, Benjamin, 1975-; Gilmour, Benjamin, 1975-; Smith, Sam (Actor); Talash, Amir Shah; Ustad, Sher Alam Miskeen; Safi, Basheer; Weda, Arzo; Khan, Inam; True, A. J. (Lightyear, 2019)
"Former Australian soldier, Mike, returns to Afghanistan to find the family of a civilian he accidentally killed during the war. Seeking forgiveness, he puts his life in the hands of the village justice system--the Jirga."--